Immunosuppressive strategies in face and hand transplantation: a comprehensive systematic review of current therapy regimens and outcomes - Huelsboemer, Lioba; Boroumand, Sam; Kochen, Alejandro; Dony, Alna; Moscarelli, Jake; Hauc, Sacha C.; Stögner, Viola A.; Formica, Richard N.; Pomahac, Bohdan; Kauke-Navarro, Martin (Frontiers in Transplantation, 2024)
Background Recipients of Vascularized Composite Allotransplants require effective immunosuppressive therapy to prevent graft rejection. This systematic review summarizes the current body of literature on immunosuppressive regimens used in face and hand transplants while summarizing their outcome in terms of rejection, renal failure, and infections. Methods A systematic search of electronic databases was conducted to identify relevant studies from 1998 until July 1st, 2023. We included all studies that discussed immunosuppressive strategies in face and hand transplant recipients according to PRISMA. Results The standard triple maintenance therapy was mostly adjusted due to nephrotoxicity or high incidence of rejection. The most common alternative treatments utilized were sirolimus (25/91; 27.5%) or everolimus (9/91; 9.9%) following hand- and photophoresis (7/45; 15.6%), sirolimus (5/45; 11.1%) or belatacept (1/45; 2.2%) following face transplantation. Episodes of rejection were reported in 60 (65.9%) of hand- and 33 (73%) of face transplant patients respectively. Graft loss of 12 (13.2%) hand and 4 (8.9%) face transplants was reported. Clinical CMV infection was observed in 6 (6.6%) hand and 7 (15.5%) face transplant recipients. Conclusions Based on the herein presented data, facial grafts exhibited a heightened incidence of rejection episodes and CMV infections. Facial mucosa adds complexity to the immunological graft composition highlighting the need of individualized immunosuppressive regimens and further research.